Value Chain Management of Orchid Businesses: A Case Study of the Indonesian Orchid Association of West Java - Salman, Tasya; Aos, Aos; Permana, Agus (AGRARIS: Journal of Agribusiness and Rural Development Research, 2024)
The orchid business in West Java can not be separated from the active role of the Indonesian Orchid Association (IOA). Currently, orchid business actors in this province have faced production problems due to their inability to meet market needs, both in quantity and quality. This study aims to identify orchid value chain management in IOA of West Java. The data collection utilized purposive and snowball sampling techniques. The respondents in this study consisted of six breeders, six growers (two seedlers and four juveniles-adults growers), six traders, and two employees of the Department of Food Crops and Horticulture of West Java. The data obtained were mapped using Porter’s value chain model. The research findings disclosed that the orchid value chain began with the procurement of inputs such as planting media, seeds, fertilizer, and pesticides. The production involved the in vitro production of plantlets using seeds obtained from crossbreeding and continued with plant enlargement. Adult and flowering plants were sold directly to consumers or through agents and traders. Two forms of governance existed within the orchid value chain. Market governance occurred between breeders and growers, growers and consumers, agents and traders, and traders and consumers. Whereas modular governance took place between breeders (imports) and industry, as well as the industry and agents. In conclusion, the value chain management of the IOA of West Java was not optimal due to the unimplemented application of tissue culture technology. Consequently, orchid production remained suboptimal and low level of orchid uniformity.